KEBUDAYAAN LAMPUNG PEPADUN DI DESA BRANTI RAYA KECAMATAN NATAR KABUPATEN LAMPUNG SELATAN (BEJULUK, PERKAWINAN, DAN PEMANGKU ADAT) - Mulyawan, Ahmad; Gafuarta, Cica; Mardianto, Doni; Paramitha, Nadya; Rahmawati, Siti; Andriyani , Yunita (LPPM Universitas Bina Bangsa, 2025)
This interview reviews the Lampung Pepadun Culture with a focus on the marriage system and traditional titles. Lampung Pepadun culture, one of Lampung's two main subcultures, has rich and unique traditions immortalized in wedding ceremonies and the use of traditional titles. This interview uses a qualitative method with an ethnographic approach, collecting data through interviews. The results of the interviews show that marriage in the Lampung Pepadun community is not only a bond between two individuals, but also between two large families, which is regulated by various stages of complex traditional ceremonies. The Lampung Pepadun traditional wedding ceremony includes a series of rituals that are rich in meaning and local wisdom, starting from the application procession to the wedding reception which is full of traditional values ​​and social norms. Apart from that, giving traditional titles in the Lampung Pepadun community is a form of respect and recognition of a person's social status in their community. Traditional titles, given based on social status and role in society, reflect the social hierarchy and cultural values ​​upheld by the Lampung Pepadun community. This study highlights the importance of understanding and preserving these traditions as part of a valuable cultural heritage, as well as their important role in strengthening community identity and solidarity.